The extra weights with two or more letters in the Syriac language and their meanings and their equivalents in the Semitic languages: (Arabic, Hebrew, Akkadian) - Karim, Safaa Farouq; Khalifa, Ammar Abdul Razzaq (Al-Adab Journal, 2022)
Our research tagged (the extra weights with two or more letters (Tawism) and their meanings and their equivalents in the Semitic languages ​​(Arabic, Hebrew, Akkadian) studies these weights by giving an overview of how these weights are formulated from the root of the original verb in order to present a simplified idea that realizes The reader through which the correct formulation of those weights and their comparison, which is an attempt to identify the nature of one of the aspects of linguistic construction through what we have of the great linguistic heritage of the sister Semitic languages ​​by comparing them to each other depending on their geographical location. On the level of linguistic structure and sentence structure, in our study we relied on the most prominent of those languages, strengthening the research with many evidences that indicate how to formulate these weights. The languages ​​were arranged according to geographical location. Those languages, starting with the more weight with the nun in the beginning, which benefits the construction of the passive, and then the aggravated (weakened) weight, which is found in all Semitic languages Adding to it the aggravated weight that benefits the construction of the unknown, and then the increased weight in the beginning (in alif or ha) which is widespread, adding to it the increased weight first (in alif or ha) that benefits the construction of the unknown, and finally the compliant weight in alif and ta